Musculoskeletal system injuries in the Polish Territorial Defence Forces - Gołuchowska, Agnieszka; Sobieszek, K (BMJ military health, 2024)
BackgroundMusculoskeletal system injuries (MSIs) are the major health problem of soldiers. The aim of this study was to assess the types of MSIs that occurred most frequently among soldiers and which parts of the body they generally affected.MethodsThe study included 140 Territorial Army soldiers, both men and women, serving in the Polish Territorial Defence Forces (TDF). Times and frequency of MSIs were assessed using an original questionnaire available via a web-based platform, the TDF Information Portal and the Yammer network.ResultsAmong the participants, 42% reported MSIs, most often a single one (19%), incurred while doing military service. Damaged muscles and ligaments were the most common injuries in both groups (p>0.05). The knee joint was the main location of injuries for both sexes (24% in men vs 50% in women, p>0.05). Other parts of the body often affected by injuries were the shoulder joint (24%, p>0.05), head, spine, wrist, fingers, ankle and feet (19% each) in the male soldiers and the ankle (24%), spine (14%), head, chest, shoulder joint and foot (10% each) in the female soldiers. Injuries reoccurred with similar frequency in the female and male soldiers (43% vs 40%, p>0.05) and had the same location in both groups (43% vs 40%, respectively, p>0.05). Difficult terrain, too intensive military training and heavy loads were the main risk factors for MSIs in both groups (p>0.05).ConclusionsMore than half of all the participants (19% of the men and 33% of the women) reported at least one injury incurred during military service. Over 40% of all the study subjects had reinjuries. The males and females were similar in terms of the most common type and location of MSI. Occurrence of MSIs rarely required interruption in the military training/service.